New approaches for antifungal susceptibility testing. (December 2017) - Sanguinetti, M.; Posteraro, B.
Abstract: Background: Invasive fungal diseases, including those caused by (multi)drug-resistant Candida and Aspergillus species, still represent global public health concerns. Information about the antifungal susceptibility testing (AFST) of fungal isolates must be quickly produced to help clinicians in administrating appropriate antifungal therapies. Unfortunately, reference AFST methods, albeit accurate, are labour-intensive and take several hours before patients' results can be available to the treating clinicians. Aims and sources: This review is a blend of evidence obtained from PubMed literature searches, clinical laboratory experience and the author's opinions that is aimed to summarize recent significant advances and ongoing challenges in the AFST area. Content: Particular attention is given to the new approaches based on genetic or phenotypic recognition of antifungal resistance that are destined to enhance the clinical usefulness of AFST in the near future. Following short-term exposures of fungal cells to antifungal drugs, new antifungal susceptibility end-points have been established, and novel diagnostic assay platforms have been proposed for the genotyping assessment of fungal isolates with resistance-associated mutations. Overall, new approaches provide a rapid, reliable means of identifying those fungal isolates with phenotypically detectable acquired resistance mechanisms, independently from the clinical susceptibility categorization of the isolates as obtained in a classical AFST way. Implications: Despite holding promise as a surrogate diagnostic method to better direct antifungal therapy, the AFST approaches described in this review need to be evaluated in multicentre laboratory studies to enable their standardization and refinement.